Resolução de problemas: um estudo sobre seu processo evolutivo nos Estados Unidos, na China e no Brasil - Hsia, Yuk Wah (2013)
The study presents results of the research community and some mathematical practices existing on the strategy of solving problems, making them accessible to teachers, in training and those working in classrooms. By exposing different views on this teaching strategy is expected to provide them with a vision of the potential of this methodology, allowing greater scope in teaching practice, which may contribute to the development of mathematical skills and abilities of their students. For this purpose, we conducted a bibliographic study that sought to weave a theoretical framework on problem solving with the characteristics inherent to the culture of three different countries: the United States, China and Brazil. The first country, sought to emphasize the historical perspective, without, however, neglecting the situation of the topic from the point of view of the grounds of cognitive theory. By tracing a historical theme throughout the twentieth century, were highlighted contributions from Polya, Dewey and Krutetskii, despite the latter being of Russian origin, provided a major boost to the constitution of the studies in this area in the United States. Approaches were highlighted on the topic regarding the teaching methodology and the results of different interpretations of the term problem solving. A list of strategies developed by Van de Walle that students can make use when solving probems. A brief history of mathematics teaching in China was presented, exposing several changes in public programs to understand the importance given to the teaching and learning of this discipline to achieve technological progress. Some results of Liping Ma s research on the knowledge of Basic Mathematics of Chinese teachers are presented. Differences between the U.S.A. and China are showed, with regard to the understanding of problem solving. The work of Brazilian groups that adopt this methodology as a line of research is highlighted, especially the GTERP of UNESP-Rio Claro, under the guidance of Onuchic, a pioneer in research on this topic. These studies gave rise to the formation of other groups in the country, which work along the same lines. The group organizes seminars that disseminate and discuss research conducted on the subject and within Brazil. The study showed that this methodology from the point of view of theory and practice, as developed in the United States is different from that made in China. It also became clear that the Chinese teachers experience the atmosphere of the teaching of mathematics in the country and 'embrace' the strategy. The study also showed that the formation of Chinese mathematics teachers have thorough training in fundamental mathematics, which is reflected in the resolution of problems in the classroom. In Brazil, despite the resolution of problems being adopted as a line of research, it was largely confined to research groups, some coming to classrooms